A method for retrieving ocean wave parameters from ZY-3 imagery. Issue 10 (2nd October 2016) - Yuan, Ce; Li, Lin; Duan, Xin-Qiao; Luo, Heng
ABSTRACT: To apply the Ziyuan-3 (ZY-3) for monitoring of sea state, this letter proposes an ocean integrated wave parameter retrieval model based on analysis of the spatial characteristics of ZY-3 satellite optical imagery. Using pseudo-top-hat operator, it retrieves significant wave height, peak wavelength and direction from ZY-3 images based on their spatial characteristics and the principles of optical shadowing of rough ocean surfaces. The experiment demonstrates the feasibility of this wave model capturing integrated wave parameters from ZY-3 images, with a maximum significant wave height error of 0.27 m and a maximum peak direction error of under the slight-moderate sea state in range 0.5–2.5 m swell waves, and the merit that the retrieval of integrated wave parameters does not depend on other measured data or the modulation transfer functions.